Creative Strategies for the Production of Texts in Elementary School Students (Docentes 2.0 Journal, 2023)
Writing is a skill that every person must acquire without distinction. Developing the student's creative writing competence affects the improvement of educational work, so it is necessary to deploy high-impact teaching strategies aimed at this goal. The research aims to analyze the educational context and propose a model of creative strategies based on the socio-formative and creative approaches. The present study was developed under the quantitative approach, statistical method, and pre-experimental design. The sample was for convenience and was represented by 52 schoolchildren. The information was collected through a questionnaire. The results have made it evident that 17.31% of students present an achievement level, such as the ability to produce texts, 57.69% present a process level, and 25% present a beginning level. The results confirm that there are difficulties for students to produce a text. It has been concluded that there is a need to implement an archetype of creative strategies based on the socio-formative and creative approach.
Keywords: Writing competence; text production; creative strategies